2023
DOI: 10.1146/annurev-publhealth-071421-045148
|View full text |Cite
|
Sign up to set email alerts
|

Climatic and Environmental Change, Migration, and Health

Abstract: The impacts of climate change, such as sea-level rise and extreme weather events, are expected to increase and alter human migration and mobility. Climate-related mobility is not inherently a crisis; it can provide a pathway for adaptation to climate change. However, a growing body of research identifies health risks and some opportunities associated with climate-related mobility. This review examines recent research (published since 2018) on the climate change–mobility–health nexus; this research focuses larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 94 publications
1
8
0
Order By: Relevance
“…Loss or damage to homes prompt migration as a strategy to find more secure housing and protect families. A study across Asia, Africa, and the Pacific supports the current findings, linking climate change impacts such as sea-level rise and extreme weather events to increased and altered human migration (Mcmichael 2023). An earlier study in the Niger Delta region of Nigeria established an association between livelihood assets, socio-economic factors, and flood hazards (Agwumafa et al 2021).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Loss or damage to homes prompt migration as a strategy to find more secure housing and protect families. A study across Asia, Africa, and the Pacific supports the current findings, linking climate change impacts such as sea-level rise and extreme weather events to increased and altered human migration (Mcmichael 2023). An earlier study in the Niger Delta region of Nigeria established an association between livelihood assets, socio-economic factors, and flood hazards (Agwumafa et al 2021).…”
Section: Discussionsupporting
confidence: 78%
“…Understanding the intersection of gender and climate change is critical for unveiling the multifaceted drivers and consequences of women's migration (Itaa et al 2023;Mcmichael 2023). This qualitative exploration seeks to illuminate the nuanced ways in which climate change influences the migration decisions of women who have fled due to a flood, remain displaced, and have chosen not to return, to avoid potential future flooding experiences in the riverine area of Bayelsa State.…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of climate change contribute to population displacement, migration and resettlement, with consequences for human health 44 . This indicator tracks population exposure to future sea level rise of one metre, and forced population displacement due to weather‐related disaster.…”
Section: Section 2: Adaptation Planning and Resilience For Healthmentioning
confidence: 99%
“…Recently, growing evidences showed that climatic conditions and changing environment are drivers of escalating migration. [67][68][69][70] Sometimes, people choose to move away from climate change vulnerability zones in response to climate change as one of the adaptation strategies, or people may be forced to migrate due to climate-related disasters. 71,72 Thus, climate change-related migration will likely reshape infectious disease profiles.…”
Section: Forcing Migrationmentioning
confidence: 99%